Improving English Language Skills Students Of Graha Yatim Dhuafa Based On Survey Results Study Interest: Peningkatan Kemampuan Bahasa Inggris Siswa Graha Yatim Dhuafa Berbasis Hasil Survey Minat Belajar - Anindita, Rina; Agustina, Noni; Simatupang, Marhisar; Prastyani, Desy; Rahman, Taufiqur (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
Community Service Activities (PKM) carried out at Graha Yatim (GRAY) Cempaka Putih, Jakarta, aim to help students in grades 5 elementary to 2 high school to have better English language skills. The activity begins with an assessment of the English language skills as well as the interests and talents of students assisted by the GRAY orphanage in learning English. Followed by activities to improve students' English skills through the language learning application "English with Noni". This activity was attended by GRAY students and accompanying teachers. Interest and talent mapping was carried out in 1 session by the Psychology Faculty team, language learning was carried out by the Teacher Training and Education Faculty. This activity will be carried out in June – July 2024, organized by the Faculty of Economics and Business, and the Faculty of Engineering. The results obtained were changes in English language skills by GRAY students. This can be seen from the English language ability scores, which were measured before and after participating in training with the English with Noni application, where the values ​​that increased were the vocabulary scores for understanding short videos, and the courage to use English in conversation. The sustainability of this program is that volunteer teachers continue learning English using the English with Noni application